2018
DOI: 10.1002/oby.22132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D Supplementation on Obesity‐Induced Insulin Resistance: A Double‐Blind, Randomized, Placebo‐Controlled Trial

Abstract: ObjectiveThe aim was to investigate whether vitamin D supplementation, combined with a hypocaloric diet, could have an independent effect on insulin sensitivity in subjects with both overweight and hypovitaminosis D. Changes from baseline in anthropometric parameters, body composition, glucose tolerance, and insulin secretion were considered as secondary outcomes.MethodsEighteen volunteers who were nondiabetic and vitamin D deficient and had BMI > 25 kg/m2 were randomized (1:1) in a double‐blind manner to a hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 33 publications
0
39
0
1
Order By: Relevance
“…Prospective studies also revealed beneficial effects of vitamin D supplementation on insulin sensitivity [ 87 , 88 ], including a meta-analysis of prospective cohort studies [ 17 , 89 , 90 ]. Intriguingly, prospective studies comparing euglycemic-hyperinsulinemic clamps at baseline and after 12 and 24 weeks of vitamin D supplementation noted improved insulin sensitivity in obese insulin-resistant subjects [ 91 , 92 ] but not in T2D subjects [ 74 ], suggesting that the established metabolic defects of T2D are not easily reversed by vitamin D repletion.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies also revealed beneficial effects of vitamin D supplementation on insulin sensitivity [ 87 , 88 ], including a meta-analysis of prospective cohort studies [ 17 , 89 , 90 ]. Intriguingly, prospective studies comparing euglycemic-hyperinsulinemic clamps at baseline and after 12 and 24 weeks of vitamin D supplementation noted improved insulin sensitivity in obese insulin-resistant subjects [ 91 , 92 ] but not in T2D subjects [ 74 ], suggesting that the established metabolic defects of T2D are not easily reversed by vitamin D repletion.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is abnormal or excessive fat accumulation and is associated with a number of metabolic disorders, such as insulin resistance, hyperinsulinemia, cancer, diabetes, dyslipidemia and cardiovascular disorders. Obesity is well known as having a high degree of morbidity and mortality [1][2][3].…”
mentioning
confidence: 99%
“…In a Central-European population, it has been suggested that genetic variability in the VDR region (including FokI and ApaI polymorphisms) may be an important factor influencing anthropometric characteristics associated with obesity including BMI, Fat Mass and body fat distribution (85). Furthermore, a study in Poland showed that the BsmI variant may be associated with BMI in men (86), but not in women (87). However, larger genome wide studies in UK (men and women) (88) and Chinese women (89) indicate that VDR genetic variants are unlikely a major determinant of obesity related phenotype such as BMI, waist circumference (WC), and waist-to-hip ratio (WHR).…”
Section: Vitamin D Receptor Genetic Variantsmentioning
confidence: 99%
“…In addition to lifestyle intervention, weightreducing surgery using gastric bypass only resulted in a temporal elevation of serum 25(OH) D 3 levels, which decreased again one month after surgery (85). Furthermore, two systematic reviews and one meta-analysis concluded that weight loss interventions showed only marginal changes in serum 25(OH)D 3 following significant weight and body fat loss (86,87). Thus, the above studies provide inconsistent evidence on the relation between AT mass and the circulating levels of serum 25(OH)D 3 .…”
Section: Vitamin D Status In the Obese Insulin Resistant Statementioning
confidence: 99%
See 1 more Smart Citation